TANAMAN HERBAL UNTUK MENGOBATI PENYAKIT DIABETES MELLITUS: LITERATUR REVIEW - Oashttamadea, Ressa; Cania, Tasya Dresi (AKADEMI PEREKAM DAN INFORMASI KESEHATAN (APIKES) IRIS PADANG, 2024)
Diabetes mellitus (DM) is a disease whose prevalence is increasing from year to year. The World Health Organization (WHO) predicts an increase in the number of diabetes patients in Indonesia from 8.4 million in 2000 to around 21.3 million in 2030. This research aims to summarize herbal plants that have been proven to have an effect on diabetes mellitus sufferers so that they can serve as a guide. for treatment of diabetes sufferers and can be used as a reference for researchers who want to research herbal plants to treat diabetes mellitus. The method used for literature studies is an article review by searching several national and international journal publications via the Google Scholar database. Based on literature studies, it is known that several plants in Indonesia have been proven to help treat diabetes mellitus because these plants contain flavonoids, polyphenols and tannins which can help lower blood sugar for diabetes sufferers.